THE NEED FOR TEACHING OCCUPATIONAL HEALTH AND SAFETY EDUCATION AS SEEN BY SECONDARY SCHOOL STUDENTS IN EGOR LOCAL GOVERNMENT AREA OF EDO STATE - Iyobo, Osayande Eric; Daniel, Aideyan Osarenwmanta (Sokoto Educational Review, 2015)
The main thrust of this paper is to appraise the need for the teaching of occupational health and safety education as seen by secondary school students in Egor Local Government Area of Edo State. Occupational safety education is an advocated subject that emphasizes on developing knowledge, skills and attitude of safety practices in any defined work environment. This has been reemphasized by the International Labour Organization (ILO), to be taken as a matter of urgency in order to enable its elementary introduction in the school system. To ascertain its relevance in secondary schools, descriptive research design was adopted and the random and systematic sampling techniques were utilized to obtain 242 students from the selected secondary schools in the Local Government Area. Self-structured questionnaires to gather information about the need for occupational safety education among students of Egor Local Government Area were used. It was revealed that the secondary schools students demonstrated a positive desire towards occupational safety education as school subject to enable them have better career choices and to practice safety measures effectively in order to avoid injuries and other work environment related hazards. It was therefore recommended that the school curriculum reform should advocate and present to the Ministry of Education and National Education Research and Development Commission the need to implement the introduction of occupational safety education in secondary schools.